Blurring societal acceptance by lack of knowledge—insights from a German coastal population study on blue carbon - Fink, Michael; Ratter, Beate (Frontiers in Climate, 2024)
Within the context of climate change, coastal vegetated ecosystems have the capacity for long-term carbon storage. Blue carbon refers to such carbon trapped in the oceans and coastal shelf seas. These ecosystems are under anthropogenic pressure and, helping these ecosystems to thrive and to realize their carbon storage potentials, interventions require acceptance from society in general and adjacent coastal communities in particular. Through a random street survey along the German coasts in 2022, quantitative and qualitative data was collected from more than 200 participants. A questionnaire comprising of 50 open and closed questions was designed to assess the status quo of German coastal residents' norms and values in relation to blue carbon ecosystems. Focus was put on nature conservation and climate change perceptions.The survey results reveal that most residents along the German coast valued nature conservation, while idealizing nature as "untouched" by humans. Responses regarding active interventions to improve coastal ecosystem services were diverse. Blue carbon strategies are likely to operate within this area of tension. Most respondents were aware of climate change as a threat to their home region and in favour of an increase in action against climate change there. The respondents were familiar with CO2 reduction and avoidance strategies. But, they were less aware of measures to remove atmospheric CO2 as well as the potential of storing CO2 in ecosystems beyond afforestation measures. Due to a lack of knowledge, no consolidated public opinions on blue carbon in coastal vegetated ecosystems could be identified, blurring societal acceptance of blue carbon strategies. While these ecosystems are particularly vulnerable to human disturbance, long-term carbon storage is essential for blue carbon. Therefore, the individual acceptance of interventions from people living in close proximity to intervention sites is key for sustained success. The study concludes on possibilities to co-create knowledge and acceptance as prerequisites for blue carbon interventions to possibly become efficacious.